2018
DOI: 10.1007/s00417-018-4023-8
|View full text |Cite
|
Sign up to set email alerts
|

Trabectome outcomes across the spectrum of glaucoma disease severity

Abstract: Trabectome surgery maintains efficacy across the spectrum of glaucoma disease severity. This particular minimally invasive glaucoma surgery procedure can be an excellent choice for subjects with moderate/advanced glaucoma as well as for early glaucoma with or without cataract surgery and is applicable to a broad patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
1
13
2
Order By: Relevance
“…A study by Ahmed et al15 using the Trabectome demonstrated a 6-month IOP of 15.7±4.0 mmHg and mean medications of 2.1±1.4, versus our observation of 15.0±3.0 mmHg and 1.2±1.4 medications.…”
Section: Discussioncontrasting
confidence: 98%
“…A study by Ahmed et al15 using the Trabectome demonstrated a 6-month IOP of 15.7±4.0 mmHg and mean medications of 2.1±1.4, versus our observation of 15.0±3.0 mmHg and 1.2±1.4 medications.…”
Section: Discussioncontrasting
confidence: 98%
“…Given the minimally invasive nature of AIT, this figure justifies its application in eyes that do not undoubtedly qualify for filtering surgery, which has a less favorable safety profile. 4 The outcomes in our patients are consistent with several recent reports. 5 Though being a simple and safe outpatient procedure with topical anesthesia, trabectome surgery has not found broad acceptance in the community due to a low predictability of success in a given case and the absence of randomized clinical trials confirming its effect and success rates.…”
Section: Discussionsupporting
confidence: 93%
“…Exfoliative glaucoma was associated with a higher success rate [26]. In a series of eyes undergoing Trabectome with or without cataract extraction, IOP lowering was similar in eyes with mild compared to moderate to severe glaucoma [25].…”
Section: Trabectomementioning
confidence: 97%
“…The Trabectome handpiece needle tip pierces the trabecular meshwork and then circumferentially ablates the trabecular meshwork for 3 to 6 clock hours. It is approved in the USA for use with and without concurrent cataract surgery and across the spectrum of disease severity and subtypes [25].…”
Section: Trabectomementioning
confidence: 99%